The Effectiveness of Retelling Technique in Improving Vocabulary Mastery: A Study in the Second-Grade Students of MAN Lombok Barat - Cahyani, Nila; Nurtaat, Lalu; Aziz, Atri Dewi (Program Studi Pendidikan Bahasa Inggris, 2025)
This study aims to investigate the effect of using retelling techniques on students’ vocabulary mastery among second-grade students at MAN Lombok Barat. A quasi-experimental research design was employed, involving two groups: an experimental group that received instruction through the retelling technique and a control group that was taught using conventional methods. The population consisted of all second-grade students, while the sample included two classes selected through purposive sampling. Data were collected using pre-test and post-test assessments to measure changes in vocabulary mastery. The results indicated a significant improvement in the experimental group’s vocabulary performance, with an average post-test score of 71.84, compared to the control group’s score of 62.08. The paired sample t-test analysis revealed a t-value of 3.583, which is higher than the critical t-table value of 2.069, leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (H₀). These findings align with previous studies by Mursilah (2016), Nursanti (2014), and Fadilaturrahmah (2022), which also reported that retelling techniques enhance students’ language skills, particularly vocabulary acquisition and comprehension. Moreover, this result supports the theoretical framework proposed by Idayani & Fitri (2021), who emphasized the effectiveness of retelling in creating a more interactive and student-centered learning environment. In conclusion, the retelling technique has a significant positive impact on students’ vocabulary mastery. Therefore, it is recommended for English teachers as an engaging and effective strategy to improve vocabulary learning outcomes.